2022
DOI: 10.3389/fcimb.2022.801569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fluoride-Resistant Streptococcus mutans Within Antagonistic Dual-Species Biofilms Under Fluoride In Vitro

Abstract: The widespread application of fluoride, an extremely effective caries prevention agent, induces the generation of fluoride-resistant strains of opportunistic cariogenic bacteria such as fluoride-resistant Streptococcus mutans (S. mutans). However, the influence of this fluoride-resistant strain on oral microecological homeostasis under fluoride remains unknown. In this study, an antagonistic dual-species biofilm model composed of S. mutans and Streptococcus sanguinis (S. sanguinis) was used to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…S. mutans was identified to play an important role in caries not only for its EPS-matrix generation ability and aciduricity but also for its cariogenicity. FR biofilms had lower pH at 275 ppm NaF at three time points, which were consistent with a previous study in which FR-related dual-species biofilms had lower supernatant pH at 275 ppm NaF whereas less difference was found at 1,250 ppm NaF (Zhang K. et al, 2022). Under low fluoride, FR may be responsible for enhanced cariogenicity depending on its better survivability and acid production under NaF, whereas the inhibitory effect of NaF on acid generation may play a dominant role at high NaF concentrations, hence less difference between FR and WT groups in addition to higher pH when compared with 275 ppm NaF.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…S. mutans was identified to play an important role in caries not only for its EPS-matrix generation ability and aciduricity but also for its cariogenicity. FR biofilms had lower pH at 275 ppm NaF at three time points, which were consistent with a previous study in which FR-related dual-species biofilms had lower supernatant pH at 275 ppm NaF whereas less difference was found at 1,250 ppm NaF (Zhang K. et al, 2022). Under low fluoride, FR may be responsible for enhanced cariogenicity depending on its better survivability and acid production under NaF, whereas the inhibitory effect of NaF on acid generation may play a dominant role at high NaF concentrations, hence less difference between FR and WT groups in addition to higher pH when compared with 275 ppm NaF.…”
Section: Discussionsupporting
confidence: 91%
“…Then, the biofilms were dehydrated using an ethanol gradient (50%, 60%, 70%, 80%, 90%, 95%, and absolute ethyl alcohol; 30 min incubation per concentration). Biofilms were dried, coated with gold-palladium, and imaged using a scanning electron microscope (SEM; Hitachi, Tokyo, Japan) at ×1,000 magnification ( Zhang K. et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with the findings of this study, we conclude that ficin controls not only bacterial biofilms but also fungal biofilms. Pre-formed biofilms show stronger resistance to stress than biofilm formation [24]. Therefore, studies have reported that antibiofilm agents, including the antifungal fluconazole, inhibit biofilm formation but do not suppress pre-formed biofilms [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-formed biofilms show stronger resistance to stress than biofilm formation [24]. Therefore, studies have reported that antibiofilm agents, including the antifungal fluconazole, inhibit biofilm formation but do not suppress pre-formed biofilms [24][25][26]. The effectiveness of ficin on both biofilm formation and pre-formed biofilm reveals its advantage over fluconazole to some extent, except for the preponderance of enzymatic degradation to control biofilms, rare resistance [13].…”
Section: Discussionmentioning
confidence: 99%